Discovery of an additional piece of the large gymnophthalmid puzzle: a new genus and species of stream spiny lizard (Squamata: Gymnophthalmidae: Cercosaurinae) from the western Guiana Shield in Venezuela - Rojas-Runjaic, Fernando J.m.; Barrio-Amorós, César L.; Señaris, J. Celsa; de La Riva, Ignacio; Castroviejo-Fisher, Santiago (Zootaxa, 2021)
Gymnophthalmids are a highly diverse group of Neotropical lizards and its species richness is still in process of discovery. The incorporation of molecular evidence and a noticeable increase in taxon and geographic sampling in systematic studies has led to the description of numerous new genera and species of gymnophthalmids (particularly in Cercosaurinae) in recent years. Herein we describe a new genus and species of cercosaurine lizard with crocodile-like morphology, from the Venezuelan Guiana Shield on the basis of molecular phylogenetic and morphological evidence. Kataphraktosaurus gen. nov. can be readily distinguished from all other genera of Cercosaurinae by a unique combination of morphological characters that includes heterogeneous dorsal scalation with enlarged and strongly keeled scales forming two paravertebral rows, ventral and subcaudal scales imbricated and strongly keeled, large and symmetrical cephalic scales, absence of postmental scale, palpebral disc translucent and divided, tail slightly compressed, all digits clawed, and only six femoral pores (three at each hindlimb) inserted in a clump of small scales. This genus is described as monotypic and only contains Kataphraktosaurus ungerhamiltoni sp. nov., which is known from one specimen and diagnosed by the same set of aforementioned characters. The secretive habits of this species and the remoteness of the locality may explain its singleton situation. Following the International Union for Conservation of Nature’s criteria, we categorized the new species as Data Deficient.